ASHÉ
1 online resource (272 pages).
Keywords: 'ASHÉ: Ritual Poetics in African Diasporic Expressivity' is a collection of interdisciplinary essays contributed by international scholars and practitioners. Having distinguished themselves across such disciplines as Anthropology, Art, Music, Literature, Dance, Philosophy, Religion, and Theology and conjoined to construct a defining approach to the study of Aesthetics throughout the African Diaspora with the Humanities at the core, this collection of essays will break new ground in the study of Black Aesthetics. This book will be of great interest to scholars, practitioners, and students interested in tracing African heritage identities throughout the African Diaspora through close examination of a variety of discourses directly connected to expressive elements of cultural production and religious rituals.